DETERMINATION OF TOTAL FLAVONOID OF n-HEXANE, ETHYL ACETATE, AND WATER FRACTION FORM CLOVE FLOWER ETHANOL EXTRACT (Syzygium aromaticum) USING UV-VIS SPECTROPHOTOMETRY METHOD - Kurnia Rahayu Purnomo Sari (Majalah Farmaseutik, 2022)
Research related to clove plants in Indonesia mostly only uses the leaves. There are still few who research phytochemical compounds in clove flowers. This study aims to determine the effect of solvent properties on the flavonoid content properties and to identify the total flavonoid content of each fraction. The three solvent fractions used include water, ethyl acetate, and n-hexane.Clove flower (Syzygium aromaticum) extraction was carried out by the maceration method using 70% ethanol. The separation of compounds based on the level of polarity was done by Liquid-liquid extraction. Determination of the flavonoid compounds was carried out qualitatively by Thin Layer Chromatography (TLC) using chloroform: methanol: glacial acetic acid (9: 1: 0.5) as mobile phase and silica gel F254 as a stationary phase with quercetin as a comparison. Quantitative analysis was performed by the UV-Vis spectrophotometry method.The results show that total flavonoid levels in the ethanolic extract of Clove flower (EEBC) were 7.818% ± 0.270, in the ethyl acetate fraction was 10.458% ± 0.516, in the water fraction was 6.137% ± 0.427, and in the n-hexane fraction was 2.251% ± 0.239. Based on these results, it can be concluded that there is a significant effect between the solvent properties of the ethanol extract and the three clove flower fractions (Syzygium aromaticum) on the total flavonoid content. The highest total flavonoid content respectively was ethyl acetate fraction, clove flower ethanol extract (EEBC), water fraction; and the n-hexane fraction.